2012
DOI: 10.5137/1019-5149.jtn.6828-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, hormonal distribution and postoperative follow up of atypical pituitary adenomas

Abstract: AIm: To assess the incidence, hormonal activity and postoperative follow up of the cases that are histopathologically diagnosed as atypical pituitary adenoma (APA) in our series. results:In histological studies, 133 cases were diagnosed as typical pituitary adenoma (91.1%) and 13 cases were APAs (8.9%) of which 10 were male (76.9%) and 3 were female (23.1%), ranged between 27 and 80 (mean 52.7) ages. Histopathological distribution of APAs was 9 nonsecretory adenomas (69.3%), 3 prolactinomas (23.1%) and 1 soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Scheithauer et al [6] reported 6 atypical cases out of 78 total pituitary adenomas, an incidence of 14.7% similar to the one reported by Zada et al [20]. In a more recent single-center study, 8.9% (13 out of 146) of pituitary adenomas were atypical, and 38.4% of them developed recurrence [21]. Apart from these reports, there are no further studies describing similar epidemiological data on ‘aggressive' pituitary tumors.…”
Section: Epidemiologysupporting
confidence: 55%
“…Scheithauer et al [6] reported 6 atypical cases out of 78 total pituitary adenomas, an incidence of 14.7% similar to the one reported by Zada et al [20]. In a more recent single-center study, 8.9% (13 out of 146) of pituitary adenomas were atypical, and 38.4% of them developed recurrence [21]. Apart from these reports, there are no further studies describing similar epidemiological data on ‘aggressive' pituitary tumors.…”
Section: Epidemiologysupporting
confidence: 55%
“…Zada et al [9] failed to find a significant difference in the recurrence rate between typical and atypical adenomas. Similarly, in a series of 16 recurrent pituitary adenomas, Yildirim et al [3] demonstrated a higher, though not statistically significant, recurrence frequency in atypical pituitary adenomas as compared to typical ones [5/13 (38.4%) and 11/133 (8.2%), respectively], though this might have been due to the relatively small sample size. …”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria for atypical adenomas include high mitotic activity, excessive p53 immunoreactivity and a Ki-67 proliferative index >3% [2]. Pituitary carcinomas are defined by craniospinal or systemic metastases, and the overall prognosis appears poor with a mean survival of 4 years following the development of metastases [3]. According to previous studies, atypical adenomas occurred in about 2.7-15% [4] and pituitary carcinomas in about 0.1-0.2% of reported cases [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, aPA is a PA with aggressive features, such as invasion, and the diagnostic criteria include increased mitotic activity, Ki-67 labeling index (LI) >3%, and extensive p53 immunoreactivity [1]. Pituitary carcinomas (PC) with poor prognosis (4-year mean survival) can be diagnosed when craniospinal or systemic metastasis is confirmed [8]. The aggressive features, however, are not well-defined and can have different interpretations, depending on the individual investigators [5,9].…”
mentioning
confidence: 99%
“…In daily practice, the aPAs that correspond to all four features are actually very rare; therefore, the predictive value of these criteria for recurrence is questionable. Moreover, a recurrence has been reported in up to 36% of typical PAs [8-14]. Aside from Ki-67 LI, definite cut-offs for increased mitotic activity and extensive p53 immunoreactivity have not been described in detail [1].…”
mentioning
confidence: 99%